Calon Tunggal Pilkada: Krisis Kepemimpinan dan Ancaman Bagi Demokrasi - Rofi Aulia Rahman; Iwan Satriawan; Marchethy Riwani Diaz (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
The single candidate became a political phenomenon in Indonesia. However, the phenomenon rarely happens, consistently increasing the number of single candidates in the local election. This research aims to analyze whether this political phenomenon alerts democracy decadency or a typical circumstance in a democratic state. The method used in this research is doctrinal legal research. The result shows several reasons the single candidate consistently increases from event-to-event sort of an epidemic virus that could spread across the province. Some factors supporting the rise of the single-candidate phenomenon, for instance, the local parliamentary threshold of proposing the candidate, public distrust to the political parties, disfunction of a political party to giving a political education for its members and constituents, and the political parties tend to avoid the political risks of losing (incumbent). Finally, this single candidate phenomenon is a bad alert for democracy development, notably in the local area.